Highly-sensitive Eu3+ ratiometric thermometers based on excited state absorption with predictable calibration. Issue 9 (17th February 2016) - Souza, Adelmo S.; Nunes, Luiz A. O.; Silva, Ivan G. N.; Oliveira, Fernando A. M.; da Luz, Leonis L.; Brito, Hermi F.; Felinto, Maria C. F. C.; Ferreira, Rute A. S.; Júnior, Severino A.; Carlos, Luís D.; Malta, Oscar L.
Abstract : Thermally excited state absorption in Eu 3+ is used to propose a new ratiometric luminescent thermometer with a predicted calibration factor. Abstract : Temperature measurements ranging from a few degrees to a few hundreds of Kelvin are of great interest in the fields of nanomedicine and nanotechnology. Here, we report a new ratiometric luminescent thermometer using thermally excited state absorption of the Eu 3+ ion. The thermometer is based on the simple Eu 3+ energy level structure and can operate between 180 and 323 K with a relative sensitivity ranging from 0.7 to 1.7% K −1 . The thermometric parameter is defined as the ratio between the emission intensities of the 5 D0 → 7 F4 transition when the 5 D0 emitting level is excited through the 7 F2 (physiological range) or 7 F1 (down to 180 K) level. Nano and microcrystals of Y2 O3 :Eu 3+ were chosen as a proof of concept of the operational principles in which both excitation and detection are within the first biological transparent window. A novel and of paramount importance aspect is that the calibration factor can be calculated from the Eu 3+ emission spectrum avoiding the need for new calibration procedures whenever the thermometer operates in different media.